Transtion-metal-free access to 2-arylphenethylamines through aryldiazonium ion catalyzed ring-opening of aziridines with arenes. (20th July 2022) - Feng, Yunqiu; Huai, Menglin; Huang, Tian; Gao, Minghui; Tao, Chuanzhou
Graphical abstract: Highlights: Aryldiazonium ions as catalysts to cleave aziridines. Access to a variety of 2-arylphenethylamines without transition metals. The cleavage of aziridines with arenes is highly regioselective. Gram-scale synthesis. Abstract: Aryldiazonium ions have been proven to catalyze effective cleavage of aziridines for the installation of varied aryl groups, providing access to a variety of 2-arylphenethylamines. This highly regioselective process, which can be performed at gram-scale, enjoys operational simplicity, as well as mild and metal-free conditions.